Jerome and the Monastic Clergy A Commentary on Letter 52 to Nepotian, with Introduction, Text, and Translation - Cain, Andrew (Leiden : BRILL, 2013)
In Jerome and the Monastic Clergy Andrew Cain provides the first full-scale commentary on Jerome's famous Letter to Nepotian along with an introduction, newly revised Latin text, and English translation
Description based upon print version of record.
Keywords: Clergy; Jerome, Saint, -419 or 420.; Monks; Nepotian, of Altinum, -396.; Jerome, -- Saint, -- -419 or 420.; Nepotian, -- of Altinum, -- -396.; Clergy; Monks; RELIGION / Institutions & Organizations; Electronic books